Contribution of Entrepreneurship to the Social Integration of People Intellectual Disabilities: A Case Study Based on the Analysis of Social Networks - Barba-Sánchez, Virginia; Salinero, Yolanda; Jiménez-Estevez, Pedro; Galindo, Esteban (Frontiers in Psychology, 2021)
In an environment characterized by high unemployment rates among people with disabilities (PwD), the objective of the present work is to analyze entrepreneurship as a labor option which fully inserts people with intellectual disabilities (PwID) into their societies. In order to carry out this research, a case study methodology based on social network analysis (SNA) has been adopted, given the nature of the variables analysed. The results indicate that the fact of having managed to start up the company has been an important source of self-confidence and inspiration, as well as increasing and intensifying the social networks of PwID involved in the entrepreneurial project.